Rapid Synthesis of Sub‐10 nm Hexagonal NaYF4‐Based Upconverting Nanoparticles using Therminol® 66. Issue 2 (25th January 2018) - Hesse, Julia; Klier, Dennis T.; Sgarzi, Massimo; Nsubuga, Anne; Bauer, Christoph; Grenzer, Jörg; Hübner, René; Wislicenus, Marcus; Joshi, Tanmaya; Kumke, Michael U.; Stephan, Holger
Abstract: We report a simple one‐pot method for the rapid preparation of sub‐10 nm pure hexagonal (β‐phase) NaYF4 ‐based upconverting nanoparticles (UCNPs). Using Therminol ® 66 as a co‐solvent, monodisperse UCNPs could be obtained in unusually short reaction times. By varying the reaction time and reaction temperature, it was possible to control precisely the particle size and crystalline phase of the UCNPs. The upconversion (UC) luminescence properties of the nanocrystals were tuned by varying the concentrations of the dopants (Nd 3+ and Yb 3+ sensitizer ions and Er 3+ activator ions). The size and phase‐purity of the as‐synthesized core and core–shell nanocrystals were assessed by using complementary transmission electron microscopy, dynamic light scattering, X‐ray diffraction, and small‐angle X‐ray scattering studies. In‐depth photophysical evaluation of the UCNPs was pursued by using steady‐state and time‐resolved luminescence spectroscopy. An enhancement in the UC intensity was observed if the nanocrystals, doped with optimized concentrations of lanthanide sensitizer/activator ions, were further coated with an inert/active shell. This was attributed to the suppression of surface‐related luminescence quenching effects. Abstract : It's fast, it's small, it's bright : Using Therminol ® 66 (T66) as a co‐solvent, bright sub‐10 nm upconverting nanoparticles (UCNPs) can easily be prepared in a highly time‐saving manner. With this protocol, core and core–shell UCNPs, excitable at both λ =795 and 976 nm, can be readily synthesized without any loss in particle quality, which highlights the versatility of T66 as a co‐solvent for UCNP synthesis.